Long-term outcomes and associated factors of Crohn's disease patients achieving transmural healing based on magnetic resonance enterography: a Chinese retrospective cohort study - Yaming Lu; Shanshan Xiong; Mengchen Zhang; Xiaoman Zu; Jinbin Li; Ren Mao; Zhirong Zeng; Xuehua Li; Minhu Chen; Yao He (SAGE Publishing, 2024)
Background: Transmural healing (TH) has emerged as a potential treatment goal for Crohn's disease (CD). However, further research is needed to confirm its benefits and risk factors associated with TH remain unclear. Objectives: We aimed to assess the value of TH based on magnetic resonance enterography (MRE) in Chinese CD patients regarding the long-term outcomes and its associated factors. Design: Retrospective, observational cohort study. Methods: Patients with CD diagnosed by colonoscopy and MRE examination between 2015 and 2022 were included. All patients were evaluated with endoscopy together with MRE within 6-12 months after baseline and followed up for at least 6 months after evaluation. The primary endpoint was the occurrence of major outcomes during the follow-up, including drug escalation, hospitalization, and surgery. The cumulative probabilities of major outcomes were calculated using Kaplan-Meier survival curves. Logistic regression analyses were used to predict TH within 6-12 months after baseline. Results: A total of 175 patients were included in the study. Of these, 69 (39.4%) patients achieved mucosal healing (MH), but only 34 (19.4%) of them achieved TH. The median follow-up duration was 17.4 months (interquartile range, 11.6-25.5), and major outcomes occurred in 58.3% of patients. A lower occurrence rate of major outcomes was noted in patients who achieved TH than in those who achieved MH only ( p  = 0.012). The baseline lymphocyte/C-reactive protein ratio (LCR) [odds ratio (OR), 1.60; 95% confidence interval (CI), 1.02-2.50; p  = 0.039] and bowel wall thickness (BWT) (OR, 0.72; 95% CI, 0.59-0.90; p  = 0.003) were independent predictors associated with TH. According to multivariate Cox regression analysis, low LCR [hazard ratio (HR), 2.34; 95% CI, 1.51-3.64; p  < 0.001], and no healing (HR, 5.45; 95% CI, 2.28-13.00; p  < 0.001) were associated with an increased risk of major outcomes. Conclusion: Patients with CD who achieved TH showed improved prognosis compared to those who achieved MH only. Baseline LCR and BWT might predict TH.